Effectiveness of a team-level participatory approach aimed at improving sustainable employability among long-term care workers: a randomized controlled trial - Heijkants, Ceciel H.; van Hooff, Madelon LM; de Wind, Astrid; Geurts, Sabine AE; Boot, Cécile RL (Scandinavian Journal of Work, Environment & Health, 2025)
' ' OBJECTIVES ': 'This study aimed to evaluate one-year effects of a team-level participatory workplace intervention on need for recovery and satisfaction of the needs for autonomy, competence and relatedness among long-term care workers by means of a randomized controlled trial. ' ' METHODS ': 'Teams of long-term care workers were randomly assigned to the intervention group (ten teams; N=78) or the wait-list control group (ten teams; N=58). The intervention consisted of a problem inventory, related to the needs for autonomy, competence and relatedness, a brainstorm towards solutions and an action plan divided over three meetings guided by a facilitator. The primary outcome was need for recovery and secondary outcomes were the satisfaction of the needs for autonomy, competence and relatedness. Outcomes were measured at baseline and after 6, 9 and 12 months. Linear mixed model analyses were performed in R. ' ' RESULTS ': 'There was no significant difference in need for recovery between groups over time. The intervention group did show a slight improvement of the satisfaction of the need for relatedness over time, while in contrast, the control group showed a decrease over time. The satisfaction of the need for autonomy and competence did not significantly differ between both groups over time. ' ' CONCLUSIONS ': 'The approach had no significant effect on the primary outcome need for recovery. The intervention did have a significant positive impact on the satisfaction of the need for relatedness, possibly because, after a period of being unable to be close, it provided opportunity to gather and work together as a team.
Keywords: autonomy; basic psychological need; care worker; competence; employability; long-term care worker; need for recovery; participatory approach; participatory workplace intervention; randomized controlled trial; relatedness; self-managing team